Structural Modifications of (1S,3S)-3-Amino-4-Difluoromethylenecyclopentanecarboxylic Acid, a Potent Irreversible Inhibitor of GABA Aminotransferase - Yuan, Hai (2007)
Low brain levels of the inhibitory neurotransmitter γ-aminobutyric acid (GABA) leads to convulsions. Inhibition of GABA aminotransferase increases the concentration of GABA and can terminate the convulsions. Earlier we reported the synthesis of (1S,3S)-3-amino-4-difluoromethylenecyclopentanecarboxylic acid (2), which is 186 times more potent an inactivator of GABA aminotransferase than the epilepsy drug S-vigabatrin. The corresponding dichloromethylene analogue of 2 (compound 3) has been made, but it shows only weak reversible inhibition of GABA aminotransferase. However, the tetrazole isostere of 2 (compound 4) has been found to be a time-dependent inactivator of GABA aminotransferase. Although it is 20 times less potent than carboxylic acid 2, it is 2.5 times more potent than S-vigabatrin. A calculation of the ClogP values indicates that 4 is the most lipophilic of the three, being 69 times more lipophilic than 2 and 55 times more lipophilic than S-vigabatrin, indicating potential for improved bioavailability.